SINERGI FILOSOFI TRI HITA KARANA DALAM PEMBELAJARAN DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Mujiburrahman, Mujiburrahman; Zahara, Laxmi; Mahsup, Mahsup; Sutajaya, Made; Suja, Wayan; Astawa, Ida Bagus Made (Realita : Jurnal Bimbingan dan Konseling, 2024)
Modern education not only focuses on the development of cognitive abilities but also emphasizes the importance of shaping students' character to be balanced spiritually, socially, and environmentally. The Tri Hita Karana philosophy, rooted in Balinese culture, provides a framework that underscores the significance of harmonious relationships between humans and God (Parahyangan), humans and others (Pawongan), and humans and nature (Palemahan). This research aims to examine the synergy between the Tri Hita Karana philosophy and the Project-Based Learning (PBL) model in creating holistic and sustainable learning. The method used in this study is a literature review, where various relevant works on Tri Hita Karana and PBL are analyzed to understand the integration of these two concepts in the educational context. The analysis is conducted by identifying how each dimension of Tri Hita Karana can be applied in PBL-based projects, as well as the impact of this synergy on students' character development. The results of this review indicate that integrating Tri Hita Karana with PBL can create a learning environment that supports students' spiritual, social, and environmental awareness development. Through PBL, students engage in real-world projects that not only enhance academic skills but also instill values of harmony with God, others, and nature. This synergy results in a more meaningful, relevant, and sustainable educational approach, where students not only improve their cognitive skills but also become socially and environmentally responsible individuals.